Deaths of Health Workers at Prof. Dr. R. D. Kandou Hospital Exposed to Coronavirus Disease-19 Period 2020-2021 - Reinhart E. Sunardibuana; Johannis F. Mallo; James F. Siwu (Medical Scope Journal, 2022)
Abstract: Coronavirus disease-19 (COVID-19) pandemic has spread to all countries, including Indonesia. This pandemic has caused a lot of losses in economic factors as well as losses of relatives including health care workers. This study aimed to determine the description of deaths among health care workers at Prof. Dr. R. D. Kandou Hospital, Manado, who were exposed to COVID-19. This was a retrospective and descriptive study using secondary data, namely all deaths of health care workers at Prof. Dr. R. D. Kandou Hospital exposed to COVID-19 in the period of 2020-2021. The results showed that there were four cases of deaths among health care workers at Prof. Dr. R. D. Kandou Hospital exposed to COVID-19 during the period 2020-2021. Three cases were over 55 years old and one case was between 25-55 years old. Three cases were male and one case was female. Four cases were medical personnel (general practitioners and specialists). Four cases had hypertension, three cases had diabetes, and one case had heart disease as comorbid. In conclusion, from the health workers at Prof. Dr. R. D. Kandou Hospital exposed to COVID-19, the majority of deaths occurred in males, aged over 55 years, medical personnel, and had hypertension as comorbid.Keywords: mortality; health care workers; coronavirus disease-19Â Abstrak: Pandemi coronavirus disease-19 (COVID-19) melanda semua negara, termasuk Negara Indonesia. Pandemi ini menyebabkan banyak kerugian, dari faktor ekonomi hingga kehilangan kerabat termasuk tenaga kesehatan. Penelitian ini bertujuan untuk mendapatkan gambaran kematian tenaga kesehatan RSUP Prof. Dr. R. D. Kandou Manado yang terpapar COVID-19. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data sekunder, yaitu seluruh data kematian tenaga kesehatan RSUP Prof. Dr. R. D. Kandou Manado yang terpapar COVID-19 periode 2020-2021. Hasil penelitian mendapatkan empat kasus kematian pada tenaga kesehatan RSUP Prof. Dr. R. D. Kandou Manado yang terpapar COVID-19 selama periode 2020-2021 yaitu tiga kasus berusia di atas 55 tahun dan satu kasus berusia di antara 25-55 tahun. Terdapat tiga kasus berjenis kelamin laki-laki dan satu kasus berjenis kelamin perempuan; kesemuanya ialah tenaga medis (dokter umum dan dokter spesialis). Empat kasus dengan komorbid hipertensi, tiga kasus dengan komorbid diabetes, dan satu kasus dengan komorbid penyakit jantung. Simpulan penelitian ini ialah pada tenaga kesehatan RSUP Prof. Dr. R. D. Kandou Manado yang terpapar COVID-19, mayoritas kematian terjadi pada laki-laki, berusia di atas 55 tahun, tenaga medis, dengan komorbid hipertensi.Kata kunci: mortalitas; tenaga kesehatan; coronavirus disease-19